CGRP antagonists and the treatment of migraine – new heroes against an old enemy - Pecikoza, Uroš (Archives of Pharmacy, 2022)
Migraine is one of the most common neurological diseases and about 20% of patients suffer from frequent episodic or chronic forms of the disease, which represent a significant global cause of chronic disability. Despite its high prevalence, the pathophysiology of migraine is still not completely understood. However, it has been known for several decades that the development of migraine attacks is dependent on the calcitonin gene-related peptide (CGRP), a neuropeptide that modulates nociceptive signaling within neuronal pathways important for migraine pain. Drugs that reduce the effects of CGRP (CGRP antagonists) have recently become available and include small-molecule CGRP-receptor antagonists (so-called gepants) that are approved for acute treatment and/or prevention of migraine attacks (ubrogepant, atogepant, rimegepant), as well as monoclonal antibodies, which are approved for prevention of migraine attacks (anti-CGRP antibodies: fremanezumab, galcanezumab, eptinezumab; anti-CGRP receptor antibody: erenumab). The effectiveness of gepants in alleviating migraine attacks is somewhat lower compared to triptans (standard drugs for treating migraine attacks), but gepants are considered safer than triptans with regard to cardiovascular side effects and the risk of medication-overuse headache. Monoclonal anti-CGRP antibodies have been shown to be useful drugs for patients who have not responded to standard prophylactic therapy (e.g., β-blockers or antiepileptics), but their high cost limits widespread use. Although the effectiveness of CGRP antagonists has been unequivocally proven, it will take time to precisely define the role of these drugs in modern migraine pharmacotherapy, and it is especially important to examine the safety of their long-term use.